The effect size of rs521851 in the intron of MAGI2/S-SCAM on HADS-D scores correlates with EAT-26 scores for eating disorders risk - Pinakhina, Daria; Kasyanov, Evgeny; Rukavishnikov, Grigory; Larin, Andrey K.; Veselovsky, Vladimir A.; Rakitko, Alexander; Neznanov, Nikholay; Kibitov, Alexander; Mazo, Galina; Artomov, Mykyta (Frontiers in Psychiatry, 2024)
An association between the MAGI2 (S-SCAM) intron variant rs521851 and depression symptoms, as measured by the depression subscale of the Hospital Anxiety and Depression Scale (HADS-D), has been recently reported. The role of MAGI2 in depression has been linked to disruptions in the gut–brain axis. In this study, we investigated the association between rs521851 and HADS-D scores in an independent cohort of 380 individuals, consisting of 238 patients with an ICD-10 diagnosis of depression and 142 healthy controls. The original association was replicated in the patient cohort but not in the control group. Further analysis revealed that the effect size of rs521851 on HADS-D scores was moderated by Eating Attitudes Test 26 (EAT-26) scores. In participants with an EAT-26 score of ≥20, the effect size of rs521851 on HADS-D was more than 20 times greater compared to those with an EAT-26 score of <20. These findings successfully replicate the original association signal for MAGI2 and HADS-D, and highlight the role of MAGI2 in gut–brain interactions.